BS ISO/IEC/IEEE 24748-3. Systems and software engineering. Life cycle management. Part 3. Guidelines for the application of ISO/IEC/IEEE 12207 (Software life cycle processes) (20th September 2019) - British Standards Institution,
No abstract available